The Blended Learning method in the teaching of vocabulary development skills to eighth graders at Colegio Dr. Ricardo Moreno Cañas, Rincón de Zaragoza, Palmares = El método de Blended Learning en la enseñanza de vocabulario a los octavos años del Colegio Dr. Ricardo Moreno Cañas, Rincón de Zaragoza, Palmares - Arias Corrales, Christofer Rolando 1992- (2017)
Acquiring vocabulary when learning English as a second or foreign language becomes one ofthe biggest challenges for leamers. The present document explores the mended Leaming strategies to facilitate the learning of vocabulary in the Costa Rican setting. This eclectic method has as its core principie the combination ofthe traditional face-to-face instruction along with the technology-enbanced class. Even though there is enough literature about the use of this method in severa) educational settings, there is not plenty information specifically on vocabulary instruction. Hence, the researchers aimed to integrate the use of this technology based methodology to the leaming of vocabulary in Efl academic settings to improve dynamicity, motivation, and engagement in the class. This study explores the roles of the teacher and tbe student under the Blended Leaming Method of instruction. To have a clear understanding of the impact of this methodology, two groups of eighth grade from a public academic high school were taught for I O lessons; one under the Blended Leaming Method (experimental group) and the other one under the traditional method of instrnction (control group). A pre-test and a post-test were applied to both groups at the beginning and at the. end ofthe intervention. Tbe resufts ofthe tests showed how the experimental group had a dramatic improvement in their vocabulary leaming in comparison with the control group. Even though botb groups presented an improvement in the mastery of their vocabuJary, the leve) of improvement was noticealt>ly bigher in the experimental group after the 1 O lessons ofintensive work. Further, the study aimed to provide an alternative to traditional instruction that offers teachers and learners a dynamrc, moüvating, and fulrfilling experience of learning. Key words: Vocabulary development skills, vocabulary learning in foreign/second language, Blended Leaming Method, BLM, vocabulary teaching strategies, BLM-Based strategies